Evaluasi Digitalisasi Layanan Aplikasi ‘Lontong Balap’ di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Almeyra, Priyanka Marsha; Firman, Firman (Prodi Ilmu Politik, 2025)
This study aims to evaluate the effectiveness of digitalized population administration services through the ‘Lontong Balap’ applications implemented by the Surabaya City Population and Civil Registration Office (Dispendukcapil). The research uses a descriptive qualitative method with an approach based on public service theory, service effectiveness theory, and government digital transformation theory. The findings show that both applications have positively impacted the efficiency and accessibility of population administration services in Surabaya. This aligns with the principles of digitalizing public services, emphasizing convenience, speed, and transparency. However, the study also identifies challenges, such as difficulties faced by the elderly in accessing digital services. Infrastructure factors also present significant barriers, particularly regarding internet network availability and skilled human resources to operate the digital system. Therefore, enhancing staff training and strengthening digital infrastructure at the sub-district level are necessary to ensure smooth application operations.